BUSINESS MODEL CANVAS ANALYSIS ON CUAL WEAVING INDUSTRY - Ayan, Syaiful; Furqon, Chairul; Sultan, Mokh. Adib (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
The purpose of this study was to describe the Business Model Canvas used by the weaving cualmaslina industry in Bangka Belitung. The type of the research used is qualitative descriptive. Data were collected through interviews, observations, and questionnaires. Data analysis was carried out through SWOT Analysis, EFAS/IFAS matrix, SWOT matrix, matrix combination of strategies and business model canvas analysis. This study found that the priority strategy that must be done by weaving cualMaslina is to utilize the product's uniqueness to attract goverment assistance and make a strong brand image to take advantage of business opportunities that are still wide open (SO). Analysis of Business Model Canvas on weaving cualMaslina found four elements that need to be improved; Customer segment forms a new segmentation, Channels works with business partners to create websites, Key activities form subdivisions of RD (quality control, design and coloring techniques), Key resources recruits HR Potential.Keyword. Business Model Canvas, analisis SWOT, EFAS/IFAS, Matriks SWOT